Food policy in 2016-2017: Food security and nutrition in an urbanizing world - Fan, Shenggen (International Food Policy Research Institute, 2017)
Together these chapters provide an overview of what we know about urbanization, food security, and nutrition and point to some of the most urgent research and data needs. They also point to promising policy directions that could begin to strengthen linkages between rural and urban areas and contribute to food security and access to nutritious foods in the world’s expanding urban areas. Addressing the needs of growing ranks of urban dwellers and improving the livelihoods of smallholder producers while promoting agricultural productivity will be essential to global food security and nutrition and to moving ahead with the new sustainable development agenda.